2017
DOI: 10.2174/1574886311666161024164859
|View full text |Cite
|
Sign up to set email alerts
|

Does Piperacillin-Tazobactam Increase the Risk of Nephrotoxicity when Used with Vancomycin: A Meta-Analysis of Observational Trials

Abstract: Adding piperacillin-tazobactam to vancomycin increases the risk of nephrotoxicity when compared to vancomycin alone or vancomycin with either cefepime or meropenem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Several studies have shown that combining PT and vancomycin leads to an increased risk of AKI, compared to the combinations of other β-lactams with vancomycin [ 7 10 ]. Multiple meta-analyses have confirmed this association among adult and pediatric patients [ 11 15 ]. This finding has been specifically demonstrated among critically ill patients who have a higher baseline risk of AKI [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies have shown that combining PT and vancomycin leads to an increased risk of AKI, compared to the combinations of other β-lactams with vancomycin [ 7 10 ]. Multiple meta-analyses have confirmed this association among adult and pediatric patients [ 11 15 ]. This finding has been specifically demonstrated among critically ill patients who have a higher baseline risk of AKI [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 92%
“…These studies found that the combination of PT and vancomycin is an independent risk factor for AKI after adjustment for potential confounders. Later, several meta-analyses confirmed the increased risk of AKI when PT was combined with vancomycin in both adult and pediatric populations [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found age was correlated with VA-AKI, yet compared with new-borns and infants age group, older age group had less OR for development of VA-AKI. Concomitant administration of diuretics, PTZ and meropenem could increase the incidence of nephrotoxicity [22,26,27], except concomitant NSAIDs seems to have a protective role for VA-AKI. In each age group, VA-AKI incidence was lower in patients with concomitant NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin (VAN) and piperacillin-tazobactam (TZP) are two of the most commonly utilized antibiotics in hospitalized patients (after the class of fluoroquinolones) (16). Meta-analyses (711) compiling over 25,000 patients suggest that VAN+TZP increases AKI by an absolute of 9% when considered against VAN + relevant comparators with mean odds ratios ranging from 1.6-3.6 fold higher risk (26). This suggested synergistic toxicity is very concerning as experts now recommend avoiding VAN+TZP (12, 13) even though VAN+TZP is a cornerstone of antibiotic therapy in numerous national guidelines.…”
Section: Introductionmentioning
confidence: 99%